Between a Granite Vase and Palace Doors. Once again about the Summer Garden by Anna Akhmatova - Михайлова, Галина (Literatūra, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The interpretation of the poem The Summer Garden, conducted within the context of the motives and images of Western European modernism, is not a particularly attractive theme for the scholars of Anna Akhmatova’s poetry. Meanwhile, a comparative study of the panchronic aspects found in The Summer Garden and of some texts by T. S. Eliot, D. Joyce and D. H. Lawrence helps to explain or even defy certain statements made by the researchers of Akhmatova’s creative work.This article deals with the relationship between these writing strategies utilized by the author and the phenomenon of the description of “time” in Akhmatova’s poetry. In view of Akhmatova’s attraction toward Western literature (especially her interest in Eliot’s, Joyce’s and M. Proust’s works), the article proposes to introduce several philosophical and aesthetic categories and metaphors (“still point,” “rose garden,” “vase”) as instruments for the study of Akhmatova’s artistic thought.The comparison of the works of Akhmatova and the European modernists is not limited to reading The Summer Garden. Some remarks also relate to the Poem Without a Hero, one part of which has an epigraph from Eliot’s Four Quartets and is associated with the transcendence of time.Tarp granito vazos ir rūmų durų. Dar kartą apie Anos Achmatovos „Vasaros sodą“Eilėraščio „Vasaros sodas“ interpretacija Europos modernizmo atstovų motyvų ir vaizdų kontekste nėra patraukli tema Anos Achmatovos kūrybos tyrėjams. Tuo tarpu „Vasaros sodo“ ir atskirų T.S. Eliot’o, D. Joyce’o ir D.H. Lawrence‘o tekstų viršlaikinojoje perspektyvoje lyginamasis tyrimas padeda paaiškinti ar net mesti iššūkį tam tikriems Achmatovos kūrybos tyrinėtojų teiginiams.Straipsnyje nagrinėjimas šių autorių meninių strategijų sąsajų su Achmatovos „laiko eigos“ fenomeno aprašymu klausimas. Atsižvelgiant į Achmatovos prisirišimą prie Vakarų kultūros ir literatūros (ypač didelis buvo jos susidomėjimas Eliot’o, Joyce’o ir M. Proust’o kūryba), straipsnyje siūloma įvesti keletą šių autorių filosofinių ir estetinių kategorijų bei metaforų ( „still point“, „rožių sodas“, „vaza“) kaip Achmatovos meninio mąstymo tyrimo įrankius.Achmatovos ir Europos modernistų lyginimas neapsiriboja „Vasaros sodo“ skaitymu. Keletas pastabų taip pat siejama su „Poema be Herojaus“, kurios viena dalis turi epigrafą iš Elioto „Keturių kvartetų“ ir siejama su laiko transcendencija.
Keywords: Akhmatova, Eliot, “Burnt Norton”, Joyce, “Dubliners”, “still point”, rose-garden, Proust